Controversial Strategies of Multinational Companies - MEGHIŞAN, Flaviu (Journal of Advanced Research in Economics and International Business; Vol 3 No 4 (2015): JAREIB, Volume III, Issue 4, 2015, 2015)
Economic science aims to the notion of effectiveness ; economy can only contribute to a reflection on equity by becoming again a moral, political science, and an economical philosophy. Within the intense conjunction, very intense in terms of international affairs, we all need morality. Certainly, multinational corporations (MNCs) may be associated with many positive aspects, all over the world. They are frontline actors on the stage of globalization. However, MNCs should not accept or take part in acts of corruption or illegal practices such as money laundering or bribery, trafficking of weapons or drugs or child labor. Some MNCs rapidly move their production facilities when there is increasing pressure of a minimum wage raising , when in fact, their responsibility is to facilitate a proper living standard of those to whom they owe their profits. Tens of millions of children work to produce cheap goods for export and 500 of the largest MNCs are jubilant for more than 70% of global commerce by providing jobs for only 0.05% of the world's population.